2022
DOI: 10.1007/s42773-022-00192-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of biochar on mycorrhizal fungi mediated nutrient uptake by coconut (Cocos nucifera L.) seedlings grown on a Sandy Regosol

Abstract: Biochar amendment of soil may ameliorate inherently infertile soils, such as in the typical coconut (Cocos nucifera L.) growth areas along tropical coasts, where, moreover, temporary moisture stress commonly occurs. We conducted a pot experiment to evaluate the effects of biochar soil amendment (1% w/w) produced from Gliricidia sepium stems (BC-Gly) and rice husks (BC-RiH) on the growth of coconut seedlings and on N and P uptake mediated by mycorrhizae under wet or dry conditions in a Sandy Regosol. The pots w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…Optimal AMF colonization is widely recognized for its ability to increase inorganic nutrients, especially P (Nirukshan et al, 2022). Several studies have indicated significant increases in P contents in the rhizosphere due to AMF effects, ranging from 54.39% to 76.13% (El-Sherbeny et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimal AMF colonization is widely recognized for its ability to increase inorganic nutrients, especially P (Nirukshan et al, 2022). Several studies have indicated significant increases in P contents in the rhizosphere due to AMF effects, ranging from 54.39% to 76.13% (El-Sherbeny et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the treatment led to a significant increase in NRA (79.5%). In addition, AMF in the biochar can be utilized as a source of N for coconut seedlings, due to reduced absorption of chemical N fertilizer (Nirukshan et al, 2022). This increase in N was due to a symbiotic system (extra radicle system), in the form of C protein pools that capture C from NO3or NH4 + from the soil (Ebbisa, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation